Dynamics of Stakeholders’ Implications in the Institutionalization of the CSR Field in France and in the United States - Avetisyan, Emma (Journal of business ethics, 2013)
This study supports the idea that fields form around issues, and describes the roles of various stakeholders in the structuring, shaping, and legitimating of the emerging field of Corporate Social Responsibility (CSR). A model of the institutional history of the CSR field is outlined, of which a key stage is the appearance of CSR rating agencies as the significant players and Institutional Entrepreneurs of the field. We show to which extent the creation and further development of CSR rating agencies, and the activism of other significant stakeholders of the field (typically portrayed as “standard setters” and “regulatory agents”), contribute to the institutionalization of CSR. With this in mind, among various stakeholders that legitimate the field of CSR, we present the efforts of global and local stakeholders such as the European Union, the United Nations, the International Organization for Standardization, and governments and their interactions. We suggest that the different paths of CSR development and institutionalization in France and in the United States depend on the nature of local and global stakeholders’ involvement in this process and their interactions.